(Table T1) Summary of permeability testing in sediments of five ODP Leg 201 sites - Kusali Gamage; Barbara A Bekins; Elizabeth J Screaton (PANGAEA, 2005)
Constant-flow permeability tests were conducted on core samples from Ocean Drilling Program Leg 201 from the eastern equatorial Pacific and the Peru margin. Eighteen whole-round core samples from Sites 1225, 1226, 1227, 1230, and 1231 were tested for vertical permeabilities. Sites 1225, 1226, and 1231 represent sediments of the open ocean, whereas Sites 1227 and 1230 represent sediments of the ocean margin. Measured vertical permeabilities vary from ~8 x 10**-19 m**2 to ~1 x 10**-16 m**2 for a porosity range of 45%-90%.
Supplement to: Gamage, K et al. (2005): Data report: Permeabilities of eastern equatorial Pacific and Peru margin sediments. In: Jørgensen, BB; D extquotesingleHondt, SL; Miller, DJ (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 201, 1-18, https://doi.org/10.2973/odp.proc.sr.201.103.2005